Weight management care practices of English and Chinese nurses. (29th October 2015) - Zhu, D.Q.; While, A.E.; Norman, I.J.; Ye, W.Q.
Abstract : Background: Obesity is a growing global public health problem which requires all healthcare professionals to deliver weight management care within their roles. Aim: To describe nurses' perceived barriers, skills and practices regarding weight‐related care and explore differences between English and Chinese nurses. Methods: A cross‐sectional, self‐administered questionnaire survey was distributed to 588 English nurses employed in a range of clinical settings and healthcare organizations and attending a large university in London (October–November 2010), and 519 Chinese nurses working in one of the largest hospitals in Shanghai, China (February–April 2011). Perceived barriers, skills and practices regarding weight‐related care were measured. Data analysis was undertaken using responses from 399 English and 466 Chinese nurses. Results: English and Chinese nurses reported similar barriers to undertaking weight‐related care practices which included two relatively new barriers, namely complex patients and the absence of clear practice guidelines. Both English and Chinese nurses reported being moderately skilled to perform weight‐related care practices with the most mean skill scores at the moderate level. Up to 11–54% of the English nurses and 10–25% of the Chinese nurses reported providing recommended weight‐related interventions for most of their patients. Generally, the English nurses reported more barriers, high‐level skills and practices regarding weight‐related care than the Chinese nurses. Limitations: The convenience samples and self‐report data may have been sources of bias. Conclusions: A variety of barriers and limited skills may help explain the suboptimal weight‐related practices among the nurses. Implications for nursing and health policy: Skill development of pre‐registration and qualified nurses is indicated as well as the development of the nurse role to include weight management care of obese patients. Evidence‐based guidelines should be readily accessible to support the nurse role in weight‐related care.